Tindak Pidana Kekerasan dalam Rumah Tangga terhadap Perempuan Korban Perkawinan Usia Dini dimasa Pandemi Covid-19 - M Zaid Sukhufan M; Yunanto Yunanto (Universitas Batanghari Jambi, 2023)
Marriage according to Law No. 1 of 1974 concerning marriage is an act that binds physically and mentally between a man and a woman as husband and wife with the aim of forming a happy family based on the Almighty God. While early marriage is a marriage in which one or both of them fall into the category under the age of 19 years, Article 1 of Law Number 23 of 2003 concerning Child Protection states that someone under 18 years is included in the category of child age. The review that will be achieved in this research is what are the factors behind the existence of violence against women victims of early marriage during the covid-19 era and how is the right legal protection for women victims of early marriage during the covid-19 period. The research method used is a qualitative research method in its implication this method is descriptive analytical. The conclusions of the research are: 1) the factors behind the violence against women victims of early marriage where covid-19 is an economic factor which is indeed in a pandemic, economic factors make everyone feel under. 2) Appropriate legal protection for women victims of early marriage during the Covid-19 period. Victims of domestic violence, most of whom are women, must receive legal protection from the state and or society in order to avoid violence or threats of violence, torture, or degrading treatment and human dignity.